VARIASI METODE DALAM PEMBELAJARAN QAWAID NAHWU UNTUK MENINGKATKAN EFEKTIVITAS PENGUASAAN TATA BAHASA ARAB - Badrul Islam; Dony Handriawan (El-Tsaqafah : Jurnal Jurusan PBA, 2025)
The learning of qawaid nahwu (Arabic grammar rules) constitutes a crucial foundation in Arabic language acquisition. However, the majority of Arabic learners face significant difficulties in mastering grammatical rules (nahwu). This is attributed to the fact that the teaching methods generally employed do not align with their linguistic and communicative needs. Based on this issue, this study aims to examine the methods used in teaching grammatical rules to provide guidance for instructors in adapting teaching strategies according to the diverse conditions and needs of learners. This study employs a descriptive-analytical method through literature review and previous research sourced from books, journals, and scientific articles discussing grammatical teaching methods. The findings reveal that there is a diversity of learning methods that can be utilized to facilitate the learning of grammatical rules. Among the most prominent are the deductive method, inductive method, modification method, activity method, and problem-solving method. This study also emphasizes the importance of selecting the most appropriate method based on learners' language proficiency levels, learning objectives, and existing learning environments. This study recommends the importance of training for Arabic language instructors for non-Arab speakers to enable them to vary teaching methods and implement modern strategies that can realize the integration of grammar mastery and linguistic communication simultaneously.